Health inequalities in hepatocellular carcinoma surveillance, diagnosis, treatment, and survival in the United Kingdom: a scoping review - Christopher Mysko; Stephanie Landi; Huw Purssell; A. Joy Allen; Martin Prince; Gary Lindsay; Steven Rodrigues; Jenny Irvine; Oliver Street; Deepankar Gahloth; Sara MacLennan; Karen Piper Hanley; et al. (BJC Reports)
Abstract Background Hepatocellular carcinoma (HCC) remains a deadly cancer in the UK despite advancements in curative therapies. Societal conditions and health inequalities influence the development of chronic liver disease and outcomes from complications including HCC. Scoping this emergent evidence-base is required to inform research and solutions for the NHS. Methods A PRISMA scoping review was performed up to September 2023. Articles exploring health inequalities in HCC involving the UK population were included. Results This review has characterised axes of health inequality and their impact across the HCC care continuum in the UK. Studies predominantly employed a cohort design or population-based analyses, with meta-analyses of surveillance utilisation including only a single UK study. These methodologies provided an appropriate lens to understand longitudinal trends and identify disadvantaged groups. However, important evidence gaps remain, including exploration of patient perspectives, intersectional analyses, and statistical measures of socioeconomic inequity in HCC. Conclusions HCC is a rapidly growing cause of cancer mortality and disproportionally affects underserved groups, presenting a major public health concern. Further research is required to innovate and evaluate surveillance and management pathways to reduce systemic inequities. Direction is needed at the national level to improve prevention, early diagnosis and access to curative treatment.